Аналіз можливості застосування дельфінотерапії для реабілітації льотного складу - Люлько, О.М.; Гудима, О.П. (Актуальні проблеми транспортної медицини, 2010)
На основе анализа данных литературы о механизме воздействия одного из методов психотерапии с привлечением дельфинов, рассматривается вопрос о возможности лечения пограничных психических расстройств функционального происхождения у летного состава. Авторы статьи делают смелый шаг по расширению немедикаментозных методов воздействия на функциональное состояние лиц ведущих профессий на транспорте. On the basis of analysis of data of literature about the mechanism of one influence of methods of psychotherapy with bringing in of dolphins, a question is examined about possibility of treatment of boundary psychical disorders of functional origin at flying composition. The authors of the article do a bold step on expansion of non drags treatment methods of affecting the functional state of persons of leading professions on a transport.